ASUHAN KEPERAWATAN KELUARGA BAPAK S KHUSUSNYA ANAK R DENGAN DISMENORE DI RT 04 RW 07 KELURAHAN LIMO KECAMATAN LIMO KOTA DEPOK - Rahma Desiani (2023)
Left untreated, painful menstruation (dysmenorrhea) significantly affects young women because it interferes with daily activities. Severe menstrual pain can be a sign and symptom of a disease such as endometriosis, which causes difficulty with reproduction and can lead to infertility by preventing the egg from migrating from the ovary to the uterus. The purpose of this study is to provide health education and provide family nursing care to children with dysmenorrhea using the nursing process strategy. In this study the researchers used a case study research design with a family nursing care approach. The results of this study are three family nursing diagnoses found in Mr. S's family, namely ineffective health management, activity intolerance and increased knowledge readiness. While the interventions carried out are adjusted to 5 family health tasks. Evaluation of the results obtained from family nursing diagnoses namely ineffective health management, activity intolerance and readiness to increase knowledge can be overcome. It is hoped that with this family nursing care can increase the knowledge and ability of the family in caring for patients with dysmenorrhea.